Identification of molecular subtypes of dementia by using blood-proteins interaction-aware graph propagational network - Park, Sunghong; Hong, Chang Hyung; Son, Sang Joon; Roh, Hyun Woong; Kim, Doyoon; Shin, Hyunjung; Woo, Hyun Goo (Briefings in Bioinformatics, 2024)
Plasma protein biomarkers have been considered promising tools for diagnosing dementia subtypes due to their low variability, cost-effectiveness, and minimal invasiveness in diagnostic procedures. Machine learning (ML) methods have been applied to enhance accuracy of the biomarker discovery. However, previous ML-based studies often overlook interactions between proteins, which are crucial in complex disorders like dementia. While protein-protein interactions (PPIs) have been used in network models, these models often fail to fully capture the diverse properties of PPIs due to their local awareness. This drawback increases the chance of neglecting critical components and magnifying the impact of noisy interactions. In this study, we propose a novel graph-based ML model for dementia subtype diagnosis, the graph propagational network (GPN). By propagating the independent effect of plasma proteins on PPI network, the GPN extracts the globally interactive effects between proteins. Experimental results showed that the interactive effect between proteins yielded to further clarify the differences between dementia subtype groups and contributed to the performance improvement where the GPN outperformed existing methods by 10.4% on average.
Keywords: Algorithms; Biomarkers; Blood Proteins; Computational Biology; Dementia; Humans; Machine Learning; Protein Interaction Mapping; Protein Interaction Maps; Alzheimer's disease; dementia subtype diagnosis; graph neural network; plasma protein biomarker; protein-protein interaction; vascular dementia